THE EFFECTIVENESS OF PROJECT-BASED LEARNING IN ENHANCING STUDENTS' CRITICAL THINKING SKILLS - Elly Purwanti; Siti Khomsiyati (Indonesian Journal of Education and Youth Development, 2025)
This study aims to determine the effect of the Problem-Based Learning (PBL) model on elementary school students' critical thinking skills. The research employed a quasi-experimental method with a Nonequivalent Control Group Design. The subjects were fifth-grade students from two different elementary schools. The instrument used was a critical thinking skills test. Data analysis revealed that students taught using the PBL model had higher critical thinking skills than those taught using conventional methods. These findings indicate that PBL is effective in enhancing elementary students' critical thinking abilities.